Lost in Transmission - Thomas Graeber; Shakked Noy; Christopher Roth (Center for Economic Studies and ifo Institute (CESifo), 2024)
For many decisions, people rely on information received from others by word of mouth. How does the process of verbal transmission distort economic information? In our experiments, participants listen to audio recordings containing economic forecasts and are paid to accurately transmit the information via voice messages. Other participants listen either to an original recording or a transmitted version and then state incentivized beliefs. Our main finding is that, across a variety of transmitter incentive schemes, information about the reliability of a forecast is lost in transmission more than twice as much as information about the forecast's level. This differential information loss predictably distorts listeners' belief updates: following transmission, reliable and unreliable messages converge in influence and average belief updates from new information are weakened. Mechanism experiments show that the differential loss is not driven by transmitters deliberately trading off the costs and benefits of transmitting different kinds of information. Instead, it results from memory constraints during transmission, which can be overcome through targeted reminders.
Keywords: 330; information transmission; word-of-mouth; narratives; reliability